Geochemistry, geochronology, and tectonic setting of early Permian ( 290 Ma) volcanic-hosted massive sulphide deposits of the Tasik Chini district, Peninsular Malaysia. Issue 8 (10th June 2016) - Basori, Mohd Basril Iswadi; Zaw, Khin; Meffre, Sebastien; Large, Robert Ross
ABSTRACT: The age and nature of Permian volcanism and sulphide mineralization in Malaysia are poorly understood. The Tasik Chini district is located in the Central Belt of Peninsular Malaysia and hosts the Bukit Botol and Bukit Ketaya volcanic-hosted massive sulphide (VHMS) deposits. These deposits are hosted by felsic-dominated Permian felsic volcanics that are part of a mixed volcano-sedimentary rock succession. Four mineralization zones were identified in both deposits: (1) stringer sulphide/zone; (2) massive sulphide zone; (3) barite zone; and (4) Fe-Mn and Fe-Si zones. The stringer and massive sulphides generally define the lower mineralized zones, whereas the barite, Fe-Mn, and Fe-Si layers define the stratigraphically upper mineralized zones. The main sulphide phases are pyrite, chalcopyrite, sphalerite, rare galena, and trace Sn-, Au-, and Ag-bearing minerals, with the latter two confined to the massive sulphide and barite zones. Trace and rare earth element data for the host rhyodacite-rhyolite at both deposits are consistent with formation in a volcanic arc palaeotectonic setting. In comparison, the trace element data for Triassic volcanic and intrusive rocks from the Tasik Chini area have moderate to low high field strength element (HFSE) concentrations along with transitional (Zr/Y = 4–7) to tholeiitic (Zr/Y = 2–4) affinities, but have similar magmatic arc signatures. Laser ablation inductively coupled mass spectrometry (LA-ICP-MS) U–Pb zircon dating of rhyolites from the Bukit Botol deposit yields early Permian (286 ± 4 to 292 ± 3 Ma) ages. Similarly, the zircon U–Pb age results for Bukit Ketaya rhyolites reveal early Permian (286 ± 2 to 288 ± 4 Ma) ages. The differences in geochemical and geochronological results between the early Permian host and the later Triassic volcanic and intrusive rocks are likely due to tectonic progression from a volcanic arc environment to a collisional setting.